Simplified Communities of Seed-Dispersers Limit the Composition and Flow of Seeds in Edge Habitats - Razafindratsima, Onja H.; Raoelinjanakolona, Nasandratra Nancia; Heriniaina, Rio R.; Nantenaina, Rindra H.; Ratolojanahary, Tianasoa H.; Dunham, Amy E. (Frontiers in Ecology and Evolution, 2021)
Edge effects, driven by human modification of landscapes, can have critical impacts on ecological processes such as species interactions with cascading impacts on biodiversity as a whole. Characterizing how edges affect vital biotic interactions such as seed dispersal by frugivores is important for better understanding potential mechanisms that drive species coexistence and diversity within a plant community. Here, we investigated how differences between frugivore communities at the forest edge and interior habitats of a diverse tropical rainforest relate to patterns of animal-mediated seed dispersal and early seedling recruitment. We found that the lemur communities across the forest edge-interior gradient in this system showed the highest species richness and variability in body sizes at intermediate distances; the community of birds showed the opposite pattern for species richness. Three large-bodied frugivores, known to be effective dispersers of large seeds, tended to avoid the forest edge. As result, the forest edges received a lower rate of animal-mediated seed dispersal compared to the interior habitats. In addition, we also found that the seeds that were actively dispersed by animals in forest edge habitats were smaller in size than seeds dispersed in the forest interior. This pattern was found despite a similarity in seed size of seasonally-fruiting adult trees and shrubs between the two habitats. Despite these differences in dispersal patterns, we did not observe any differences in the rates of seedling recruitment or seed-size distribution of successful recruit species. Our results suggest that a small number of frugivores may act as a potential biotic filter, acting on seed size, for the arrival of certain plant species to edge habitat, but other factors may be more important for driving recruitment patterns, at least in the short term. Further research is needed to better understand the potential long-term impacts of altered dispersal regimes relative to other environmental factors on the successional dynamics of edge communities. Our findings are important for understanding potential ecological drivers of tree community changes in forest edges and have implications for conservation management and restoration of large-seeded tree species in disturbed habitats.